138 Working with service users and our local community to co-design an inclusive and person-centred hospice day service. (14th March 2023) - Richardson, Lorna; Haugh, Michael; Stanley, Sarah; Charles, Kate; Hawkins, Hayley; Chapman, Laura
Abstract : Background: With an ageing population the need for palliative care services is set to rise. 1 Whilst there is no clear definition of palliative care day services, traditionally they offer a range of physical, psychosocial and spiritual services to enhance quality of life. 2 However the Covid19 pandemic has presented challenges whilst also highlighting opportunities for innovation in many areas of palliative care, including day services. 3 There is currently limited evidence to suggest what service users want from a palliative care day service, and as we emerge from the pandemic there is a unique opportunity to develop a new place-based service in our locality. Aim(s): To identify areas for improvement in our hospice day services and to understand how the service can become more inclusive and person centred. Methods: As part of the re-development of our hospice day service we have created an electronic questionnaire. This was developed by day service staff with the input of therapy, senior management and research teams. The questionnaire is designed for hospice service users (patients and carers) and non-service users (people from our local community), and looks to identify what our day services should offer in terms of activities and accessibility. Results: We received thirty-two responses, the majority (n=17) from people living with a terminal illness. Participants highlighted a number of areas for improvement. Using the survey results we are working to adapt our services to provide a more inclusive and accessible hospice day service. Conclusions: When considering the re-development of a service it is important to consider the needs of the current service user and the local community. The results of this questionnaire have helped us to begin co-designing a more inclusive and person-centred approach to day services, which we hope will suit the needs of those using the service both now and in the future. References: World Health Organization, 2018. Palliative care fact sheet. Geneva: WHO. Hasson F, Jordan J, McKibben L. et al . Challenges for palliative care day services: a focus group study. BMC Palliat Care 2021;20 :11. https://doi.org/10.1186/s12904-020-00699-7 Dunleavy L, Preston N, Bajwah S, Bradshaw A, Cripps R, Fraser LK, Maddocks M, Hocaoglu M, Murtagh FE, Oluyase AO, Sleeman KE, Higginson IJ, Walshe C. 'Necessity is the mother of invention': Specialist palliative care service innovation and practice change in response to COVID-19. Results from a multinational survey (CovPall). Palliat Med . 2021 May;35 (5):814–829. doi: 10.1177/02692163211000660. Epub 2021 Mar 23. PMID: 33754892; PMCID: PMC8114457.